Simple Synthesis of γ‐Spirolactams by Birch Reduction of Benzoic Acids. Issue 6 (10th February 2017) - Krüger, Tobias; Kelling, Alexandra; Schilde, Uwe; Linker, Torsten
Abstract : A convenient synthesis of γ‐spirolactams in only two steps was developed. Birch reduction of benzoic acids and immediate alkylation with chloroacetonitrile afforded cyclohexadienes in high yields. The products could be isolated by crystallization on a large scale in analytically pure form. Subsequent hydrogenation with platinum(IV) oxide as the catalyst reduced the nitrile functionality and the double bonds in the same step with excellent stereoselectivity. The relative configurations were determined unequivocally by X‐ray analyses. Direct cyclization of the intermediary formed amino acids afforded the desired γ‐spirolactams in excellent overall yields. The procedure is characterized by few steps, cheap reagents, and can be performed on a large scale, interesting for industrial processes. Abstract : Reduction + reduction: This simple sequence allows the synthesis of γ‐spirolactams3 from commercially available benzoic acids1 via cyclohexadienes2 in only two steps. The method is characterized by cheap reagents, good to high yields, and excellent diastereoselectivities, and the products can be isolated by crystallization on a large scale.